An Experimental Work on “Partial Replacement of Cement with Marble Dust Powder in Concrete” - Bakhtiyar Ahmed, Jiji M. Thomas, Pushpendra Kumar (International Journal of Advanced Science and Technology, 2020)
Strong achievement is being made all over the world towards in the advancement of clean energy for environmental protection and arrange energy consumption pattern to meet its increasing demand. The grid is to be design or upgraded to promote clean energy, control the energy consumption pattern and bring security to grid. The smart grid will achieve these requirements. The developments in information and communication technology support the smart grid vision and mission. Sensor and control automation also support the up-gradation of existing grid to smart grid. There are many objection and issues in the implementation of smart grid. This research paper presents Smart grid challenges, issues and concept with solutions. Keywords: Machine Learning, Decision Tree, Confusion Matrix, Train and Test Split Ratio, Weka Tool, Accuracy.